How Does the L884P Mutation Confer Resistance to Type-II Inhibitors of JAK2 Kinase: A Comprehensive Molecular Modeling Study - Xiaotian Kong (Nature Portfolio, 2017)
Abstract Janus kinase 2 (JAK2) has been regarded as an essential target for the treatment of myeloproliferative neoplasms (MPNs). BBT594 and CHZ868, Type-II inhibitors of JAK2, illustrate satisfactory efficacy in preclinical MPNs and acute lymphoblastic leukemia (ALL) models. However, the L884P mutation of JAK2 abrogates the suppressive effects of BBT594 and CHZ868. In this study, conventional molecular dynamics (MD) simulations, umbrella sampling (US) simulations and MM/GBSA free energy calculations were employed to explore how the L884P mutation affects the binding of BBT594 and CHZ868 to JAK2 and uncover the resistance mechanism induced by the L884P mutation. The results provided by the US and MD simulations illustrate that the L884P mutation enhances the flexibility of the allosteric pocket and alters their conformations, which amplify the conformational entropy change (−TΔS) and weaken the interactions between the inhibitors and target. Additionally, the structural analyses of BBT594 and CHZ868 in complex with the WT JAK2 illustrate that the drug tail with strong electronegativity and small size located in the allosteric pocket of JAK2 may enhance anti-resistance capability. In summary, our results highlight that both of the changes of the conformational entropies and enthalpies contribute to the L884P-induced resistance in the binding of two Type-II inhibitors into JAK2 kinase.